Peacebuilding amongst Christian and Muslim in Nigeria : a critical study of "a model of and for" religion leaders as peace brokers - Umar Silas, Labilam (Stellenbosch : Stellenbosch University, 2016)
Thesis (MTh)--Stellenbosch University, 2016.